The impact of peer effects on adolescents' physical exercise: a meta-synthesis study - Chen, Kai; Chen, Cheng; Yang, Jincheng; Li, Zhongdong (Frontiers in Psychology, 2026)
This study employed a meta-synthesis approach to systematically review qualitative and mixed-methods research on the influence of peer effects on adolescents' physical exercise behavior, aiming to provide a theoretical basis and practical pathways for promoting adolescent sports health. Through literature screening and quality assessment, 28 articles were included, yielding 45 research findings. These were categorized into 12 subcategories and synthesized into four main integrated findings: Peer Support and Interaction; Behavioral Modeling and Atmosphere; Intrinsic Motivation and Identity; and Educational Interventions and Risk Management. The study found that peer effects significantly influence adolescents' participation and persistence in physical exercise through multiple pathways, including emotional support, behavioral modeling, and motivational atmosphere. However, potential risks such as dependency and group heterogeneity exist. Future educational practices should emphasize differentiated guidance, establish scientific peer support systems, effectively mitigate potential risks while leveraging positive effects, and promote the long-term healthy development of adolescents' physical activity behaviors.